Gender Gaps at the Enterprise Level : Evidence from South Africa - Campos, Francisco (World Bank, Washington, DC, 2016)
Female-owned small to medium businesses in the Western Cape Province in South Africa are less productive, generate lower revenues and have less employees than male-owned enterprises. In this brief, we use the baseline survey for an impact evaluation of a business development services program to identify why these differences exist and explore paths towards policy interventions to overcome them. Author conclude that the concentration of businesses in low performing sectors, the lack of commitment to the business, the intertwining of household and business responsibilities, and access to finance can be important barriers to the growth of women-headed enterprises. Author suggests targeted alternative interventions to address these constraints and recommend comparing their effectiveness through rigorous evaluations. Author argue that the gender differences identified in the performance of Small, Medium, and Micro Enterprises (SMMEs) in this Province of South Africa can be due to a combination of: 1) the concentration of women-entrepreneurs in a small number of low-performing sectors, 2) firms being seen by entrepreneurs as an interim solution, 3) the intertwining of household and enterprise money, and 4) credit constraints.